Disordered eating behaviors, depression, anxiety and stress among Malaysian University students. - Gan, W.Y.; Mohd Taib, Mohd Nasir; Mohd Shariff, Zalilah; Abu Saad, Hazizi (2011)
The aim of this study was to examine the relationships between depression, anxiety and stress with disordered eating among university students. The Eating Attitudes Test-26 (EAT-26) and Depression, Anxiety and Stress Scale-21 (DASS-21) were administered on 584 Malaysian university students (59.4% females and 40.6% males). About one in five participants (18.2%) were at risk of eating disorders. Females had significantly higher proportion of at risk of eating disorders (21.3%) compared to males (13.5%). There was no sex difference in mean EAT-26 scores. The prevalence of depression, anxiety and stress of moderate severity or above were 29.3%, 55.0% and 21.6% respectively. No sex differences in depression and anxiety scores were found but females had significantly higher stress score compared to males. There was significant relationship between EAT-26 and DASS-21 subscales. Further, no significant interaction effect was found for sex and ethnicity with EAT-26 and DASS-21 subscales. The prevalence of at risk of eating disorders, depression, anxiety and stress among university students were high. There were positive correlations between depression, nxiety, and stress with disordered eating. Further studies on their associated risks are warranted.